2014
DOI: 10.1177/1934578x1400900706
|View full text |Cite
|
Sign up to set email alerts
|

Abietane Diterpenoids from Clerodendrum trichotomum and Correction of NMR Data of Villosin C and B

Abstract: Nine abietane diterpenoids (1–9) were isolated from the stems of Clerodendrum trichotomum Thunb. and identified by spectroscopic methods. Furthermore, corrected NMR data is provided for Villosin C (1) and B (2) whose absolute configurations were elucidated from circular dichroism (CD) data. All isolates were tested for cytotoxicity against four cancer cell lines (A549, HepG-2, MCF-7 and 4T1). Compounds 1, 2, 3, 4 and 8 were found to have remarkable cytotoxic effects with IC50 values ranging from 8.79 to 35.46 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Eleven compounds were identified, including seven abietane diterpenes: sugiol (18) , teuvincenone A (48) , teuvincenone B (89) , teuvincenone F (10) , teuvincenone H (88) , uncinatone (9) and cyrtophyllone B (21) [ 94 ]. In further studies on C. trichotomum stems, the same authors also identified the diterpenoids villosin B (90) and villosin C (85) ; these demonstrate remarkable cytotoxic activities against tumour cell lines A549, HepG-2, MCF-7 and 4T1 with IC 50 values ranging from 14.93 to 29.74 µM [ 95 ].…”
Section: A Review Of Diterpenoid Compounds Isolated From Cl...mentioning
confidence: 99%
See 1 more Smart Citation
“…Eleven compounds were identified, including seven abietane diterpenes: sugiol (18) , teuvincenone A (48) , teuvincenone B (89) , teuvincenone F (10) , teuvincenone H (88) , uncinatone (9) and cyrtophyllone B (21) [ 94 ]. In further studies on C. trichotomum stems, the same authors also identified the diterpenoids villosin B (90) and villosin C (85) ; these demonstrate remarkable cytotoxic activities against tumour cell lines A549, HepG-2, MCF-7 and 4T1 with IC 50 values ranging from 14.93 to 29.74 µM [ 95 ].…”
Section: A Review Of Diterpenoid Compounds Isolated From Cl...mentioning
confidence: 99%
“…The combined extracts were filtered and the solvent was removed under vacum to obtain a crude extract. Villosin B (90) Villosin C (85) Cyrtophyllone B (21) Uncinatone (9) Teuvincenone B (89) Sugiol (18) Teuvincenone F (10) Teuvincenone A (48) Teuvincenone H (88) [ 95 ] C. trichotomum Roots Cut and air-dried roots were extracted under reflux with 95% EtOH Extract was filtered and organic solvents evaporated to receive the crude residue 15,16-dehydroteuvincenone G (91) 3-dihydroteuvincenone G (92) 17-hydroxymandarone B (93) Trichotomin A (94) 15,16-dihydroformidiol (95) 18-hydroxyteuvincenone E (96) 2α-hydrocaryopincaolide F (97) 15α-hydroxyuncinatone (98) 15α-hydroxyteuvincenone E (99) Trichotomin B (100) Trichotomside A (101) Trichotomside B (102) [ 96 ] …”
Section: A Review Of Diterpenoid Compounds Isolated From Cl...mentioning
confidence: 99%
“…[ 1 ] Previous chemical studies on this genus resulted in the characterization of several diterpenoids exhibiting diverse biological activities including antibacterial, antioxidant, antiinflammatory, antidiabetic, antihypertensive, cytotoxic, and anti‐asthmatic properties. [ 2‐11 ] Clerodendrum chinense var . simplex , an ethnomedicinal plant of the Dai minority in China, has been used for the treatment of rheumatic arthritis, hypertension, erysipelas, and chronic osteomyelitis.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…3 The major constituents reported include phenylpropanoids, terpenoids, flavonoids and steroids. [4][5][6][7] In earlier work, 5,7 the chemical constituents of the ethyl acetate fraction from the stems of C trichotomum have been studied systematically. However, relatively few papers have been devoted to the n-butanol extract so far.…”
Section: Introductionmentioning
confidence: 99%
“…Abietane diterpenoids are characteristic constituents of the genus Clerodendrum, which exhibit remarkable antitumor, 8 antiinflammatory, 9 and insecticidal activities. 10 This paper focused on the study of the chemical constituents from the n-butanol extract of C trichotomum stems, and 2 new abietane diterpenoids, (4S, 5S, 10S)-12-(β-D-glucopyranosyl)oxy-11-hydroxyabieta-8,11,13-triene-19-oic acid β-D-glucopyranosyl-(1→6)-β-D-glucopyranosyl ester (1), and (3S, 5S, 10S, 15S)-3β-[β-D-glucopyranosyl-(1→6)-β-D-glucopyranosyl]oxy-12-(β-D-glucopyranosyl)oxyabieta-8,11,13-triene-11,16-diol (2), along with 5 known terpene glycosides (3)(4)(5)(6)(7) were isolated and characterized (Figure 1, 1-7). Compounds 1-7 were evaluated for cytotoxicity against several cancer cell lines, and all of them were inactive.…”
Section: Introductionmentioning
confidence: 99%